The Risk of Recrystallization: Changes to the Toxicity and Morphology of Pyrimethamine - Zak Perold; Mino R Caira; Marius Brits (Frontiers Media S.A., 2014)
PURPOSE. Pyrimethamine, an anti-malarial agent known to exhibit solid state polymorphism, may be purified by means of recrystallization. Recrystallization may alter the solid state chemistry of pharmaceuticals, which may impact the toxicity and/or manufacturability thereof. We evaluated the risks associated with the recrystallization of pyrimethamine. METHODS. Pyrimethamine was recrystallized using several organic solvents. X-ray diffraction, thermal analysis, infra-red spectroscopy, microscopy, flowability -, solubility and dissolution testing as well as computational work were employed to evaluate the recrystallized products. RESULTS. A toxic solvatomorph of pyrimethamine (Pyr-MeOH) was found to be the product from methanol recrystallization. The elucidation of - and the elaboration on the unique characteristics of Pyr-MeOH provides the pharmaceutical industry with several means to identify Pyr-MeOH and to distinguish it from the pharmaceutically preferred anhydrous form (Pyr). Thermal methods of analysis found that the toxicity of Pyr-MeOH may be reversed by overcoming a desolvation activation energy of 148 kJ/mol. In addition it was found that recrystallization altered the morphology of Pyr. Angle of repose and tapped density determinations identified that the different morphologies of Pyr displayed differences in powder flow and compressibility behaviour and In Silico calculations were successful in rendering morphologies resembling that found experimentally. CONCLUSION. We present a solvatomorph of pyrimethamine and provide several characteristic means to identify this unwanted toxic form and quantified the energy required to overcome its toxicity. In addition we describe that Pyr may present in different morphologies and show how it may impact the manufacturability thereof.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.